Pengaruh Pengembangan Karakter Siswa SD PLTU Suralaya Wukir Retawu Kelas VI untuk Berpikir Kritis di Era Generasi Alpha - Dela Ardianti; Desty Endrawati Subroto; Jihan Rohadatul Aisy; Muhamad Dai Azizi; Wulandari Nurhazriyah (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the relationship between character education and critical thinking skills of the alpha generation in order to become intelligent and characterful individuals to compete globally. This study uses a literature analysis method. The results show that character education involves three main aspects: understanding good values ​​(knowing the good), loving good values ​​(loving the good), and implementing good values ​​(acting the good). Character education is an important element in forming individuals with integrity and noble character. In the digital era, the influence of social media, wide access to information, and technology emphasize the need for more relevant character education. This study examines the role of character education, the challenges faced, and strategies to overcome them through a holistic approach involving families, schools, and communities with wise use of technology .